Insights into active tungsten species on Pt/W/SBA-15 catalysts for selective hydrodeoxygenation of glycerol to 1,3-propanediol - Bhowmik, Susmita; Enjamuri, Nagasuresh; Sethia, Govind; Akula, Venugopal; Marimuthu, Banu; Darbha, Srinivas (Molecular Catalysis, 2022)
Diols are important class of industrial chemicals. Their synthesis from bio-resources (instead from fossil feed-stocks) is sustainable. In this study, we probed active tungsten species on Pt/W/SBA-15 catalysts for selective synthesis of 1,3-propanediol (1,3-PDO) from aqueous glycerol through a liquid-phase hydrodeoxygenation re-action. A synergistic enhancement in glycerol conversion and 1,3-PDO selectivity was observed when both Pt and W were present on the catalyst. A volcano-shape variation followed with a gradual increase in glycerol conversion and 1,3-PDO yield with W-loading (0.25-15 wt%) was observed. Pt dispersion and acidity of the catalyst dis-played similar variations with the W-loading confirming their critical role in the reaction. Structure-function relationships inferred that oligomeric WOx with moderate Bro center dot nsted acidity (predominant at 1 wt% W-loading) in contact with dispersed Pt are the active species for 1,3-PDO formation and crystalline WO3 with strong Bro center dot nsted acidity (prevalent above 4 wt% W-loading) in association with Pt nanoparticles lead to 1-propanol formation.
Keywords: 3-Propanediol; Active sites; Glycerol; Hydrodeoxygenation; Hydrogenolysis; Supported Pt-WO x